The Customer Perception Influence The Purchase Intention Of Milo Breakfast Cereals - Ai Peng, Chan (Universiti Teknikal Malaysia Melaka, 2018)
As what show in chapter 1,the eating habit in the recent years have changed the customer perception on breakfast cereals in Malaysia.Customer perception is very important in the purchase intention.Customer perception are considered as the perception of a customer towards a products or service including perceived price,perceived quality and perceived value.The customer perception will influence the purchase intention such as brand awareness and customer satisfaction.Besides,the awareness of public to the quality of breakfast cereals which is rise in our country.In the price aspect the customer will also concern and made comparison before they buy the MILO breakfast cereal.Customers now also concern about the perceived value if compare to before.Hence,it is important for the research to be carried to identify which factors of the customer perception is crucial for the MILO breakfast cereals to lead them into succeed.